Ketamine for bipolar depression: an updated systematic review - Farhan Fancy; Sipan Haikazian; Danica E. Johnson; David C. J. Chen-Li; Anastasia Levinta; Muhammad I. Husain; Rodrigo B. Mansur; Joshua D. Rosenblat (SAGE Publishing, 2023)
Background: The therapeutic potential of subanesthetic doses of ketamine appears promising in unipolar depression; however, its effectiveness in treating bipolar depression (BD) remains uncertain. Objective: This systematic review aimed to summarize findings on the use of ketamine for the treatment of BD by assessing its efficacy, safety, and tolerability. Design: Systematic review. Methods: We conducted a systematic review of studies that investigated the use of ketamine for adults with BD. We searched PubMed and Embase for relevant randomized-controlled trials, open-label trials, and retrospective chart analyses published from inception to 13 March 2023. Results: Eight studies were identified [pooled n  = 235; mean (SD) age: 45.55 (5.54)]. All participants who received intravenous (IV) ketamine were administered a dose of 0.5-0.75 mg/kg as an adjunctive treatment to a mood-stabilizing agent, whereas participants who received esketamine were administered a dosage ranging from 28 to 84 mg. Flexible dosing was used in real-world analyses. A total of 48% of participants receiving ketamine achieved a response (defined as ⩾50% reduction in baseline depression severity), whereas only 5% achieved a response with a placebo. Real-world studies demonstrated lower rates of response (30%) compared to the average across clinical trials (63%). Reductions in suicidal ideation were noted in some studies, although not all findings were statistically significant. Ketamine and esketamine were well tolerated in most participants; however, six participants (2% of the overall sample pool, 5 receiving ketamine) developed hypomanic/manic symptoms after infusions. Significant dissociative symptoms were observed at the 40-min mark in some trials. Conclusion: Preliminary evidence suggests IV ketamine as being safe and effective for the treatment of BD. Future studies should focus on investigating the effects of repeated acute and maintenance infusions using a randomized study design.